20 Years in the world of work: A study of (nonstandard) occupational trajectories and health. (March 2019) - Giudici, Francesco; Morselli, Davide
Abstract: Longitudinal research emphasizes that nonstandard (i.e., temporary contracts, part-time and multiple jobs) and discontinuous occupational trajectories (i.e., intermittent unemployment or inactivity) are associated with lower levels of mental health. A branch of this research highlights, over many years of observation the importance of the time of exposure to nonstandard occupational trajectories as a social determinant of health. However, the timing of the observed period and the multidimensionality of nonstandard occupational trajectories have been highly neglected. In this study, we analyze the Swiss Household Panel data, which used a life history calendar to collect occupational trajectories across the lifespan. The data included the trajectories of 5690 initially healthy Swiss residents and were used to reconstruct the occupational trajectories during the first 20 years in the world of work. A sequence analysis revealed eight distinct types of occupational careers based on three dimensions: type of contract, labor market status and number of simultaneous jobs. The results show that discontinuous occupational trajectories (characterized by continuous jumps between temporary work, long periods of unemployment, social help, inactivity or part-time work) are associated with higher depressive symptoms, lower life course mental health and lower self-reported health during an individual's first 20 years in the world of work. Highlights: Discontinuous careers are formed by repeated spells of non-standard jobs. Discontinuous careers are not just a stepping stone into the world of work. Discontinuous careers are associated to lower health.